Application of The Contextual Teaching And Learning (CTL) Learning Model Using Public Service Advertising Video Media On Explanation Text Writing Skills Class VI Students of MI Attaqwa Kalanganyar Karanggeneng Lamongan - Husni Abdillah; Nisaul Barokati Selirowangi (JIEES : Journal of Islamic Education at Elementary School, 2023)
This research is motivated by the problem of the number of students who do not complete explanatory texts. This is because the learning model used is still conventional, and the teacher is not maximal in using learning media in explanatory text material. With these conditions, students are passive and unmotivated in participate in learning, which has an impact on student learning outcomes. Based on these problems, the researchers took the formulation of the problem regarding (1) the application of the model, (2) the completeness of student learning outcomes, and (3) student responses. The purpose of this research is to find out how effective the application of the Contextual Teaching and Learning (CTL) learning model is by using public service advertisement videos as learning media in explanatory text material in terms of model application, student learning outcomes, and student responses. This study uses a mixed research method, namely qualitative and quantitative research that is descriptive. The data collection techniques used are (1) observation techniques, (2) tests, and (3) questionnaires. The results of this study indicate that the application of the Contextual Teaching and Learning (CTL) learning model using media video advertisements for public services is effective for use in explanatory text material for class VI MI Attaqwa Kalanganyar, Karanggeneng Lamongan in terms of the percentage value (1) the application of the model is 88.53%, (2) student learning completeness is 84%, and (3) student response is 83.66%.